Sex and the office : women, men, and the sex partition that's dividing the workplace - Elsesser, Kim (Taylor Trade Publishing, 2015)
"In Sex and the Office, Kim Elsesser delves into how issues as varied as sexual harassment, workplace romance, spousal jealousy, and communication styles create barriers between men and women at work. These invisible barriers, which Elsesser labels the "sex partition," tend to have the greatest impact on the careers of women, because men typically still dominate senior management, and connections with senior managers are essential for career advancement. Elsesser describes how senior male employees prefer to stick with other men, especially when it comes to dinners, drinks, late-night meetings, or business trips. When it's time for promotions or pay raises, these same executives are more likely to show preference to the employees with whom they feel most comfortable--other men. Elsesser doesn't blame men for the sex partition; instead, she describes how some common organizational practices create barriers between the sexes. She offers practical advice on how to break down the sex partition and reveals the best strategies for networking with the opposite sex. Sex and the Office is sure to spark new dialogue on the sources of the gender gap at work. "--